Impact of cultural diversity on wages and job satisfaction in England - Longhi, Simonetta (Colchester, 2011)
"This paper combines individual data from the British Household Panel Survey and yearly population estimates for England to analyse the impact of cultural diversity on individual wages and on different aspects of job satisfaction. Do people living in more diverse areas have higher wages and job satisfaction after controlling for other observable characteristics? The results show that cultural diversity is positively associated with wages, but only when cross-section data are used. Panel data estimations show that there is no impact of diversity. Using instrumental variables to account for endogeneity also show that diversity has no impact."